Review of the book by Konrad Paul Liessemann - Ivana Gačanović (University of Belgrade, 2016)
Review of the book by Konrad Paul Liessemann, Teorija neobrazovanosti: Zablude društva znanja. [The Theory of Miseducation]. 2008. Zagreb: Jesenski i Turk